A Retrospective Cohort Study of Cobra Envenomation: Clinical Characteristics, Treatments, and Outcomes - Tansuwannarat P. (2023)
This study investigated the clinical characteristics, treatments, and outcomes of envenomation involving cobra species in Thailand (Naja kaouthia, Naja siamensis, and Naja sumatrana). Data of patients who had been bitten by a cobra or inoculated via the eyes/skin in 2018-2021 were obtained from the Ramathibodi Poison Center. There were 1045 patients admitted during the 4-year study period (bite, n = 539; ocular/dermal inoculation, n = 506). Almost all patients with ocular/dermal inoculation had eye involvement and ocular injuries, but none had neurological effects. Most of the patients bitten by a cobra had local effects (69.0%) and neurological signs and symptoms (55.7%). The median interval between the bite and the onset of neurological symptoms was 1 h (range, 10 min to 24 h). Accordingly, patients should be observed closely in hospitals for at least 24 h after a bite. Intubation with ventilator support was required in 45.5% of patients and for a median duration of 1.1 days. Antivenom was administered in 63.5% of cases. There were nine deaths, most of which resulted from severe infection. Neurological effects and intubation were significantly more common after a monocled cobra bite than after a spitting cobra bite. The administration of antivenom with good supportive care, including the appropriate management of complications, especially wound infection, might decrease fatality.